2003
DOI: 10.1080/03031853.2003.9523619
|View full text |Cite
|
Sign up to set email alerts
|

Contractual Relationships Between Small-Holder Sugarcane Growers and Millers in the Sugar Industry Supply Chain in Swaziland

Abstract: This paper proposes and analyses a model of relationships between smallholder sugarcane growers and millers in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Relational commitment is defined as the extent to which trading partners devote time and resources to the ongoing trade relationship since they consider the relationship to be important [82]. It is a measure of the strength of the business relationship and explains the survival of the relationship in turbulent times [90]. Where relationships are characterized by a high level of commitment, parties are willing to enter transaction-specific investments that support business resilience.…”
Section: The Nature Of Farmer-buyer Relationshipsmentioning
confidence: 99%
“…Relational commitment is defined as the extent to which trading partners devote time and resources to the ongoing trade relationship since they consider the relationship to be important [82]. It is a measure of the strength of the business relationship and explains the survival of the relationship in turbulent times [90]. Where relationships are characterized by a high level of commitment, parties are willing to enter transaction-specific investments that support business resilience.…”
Section: The Nature Of Farmer-buyer Relationshipsmentioning
confidence: 99%
“…These actions may be a disincentive to some members, which may result in failure to reach goals, and even in coordination break up (Olson, 2009). Farmer groups can only be successful is they are based on trust, honesty, mutual respect and commitment to the group (Masuku et al, 2003). This brings out the suggestion that when choosing group members, notably farmers who are working towards the same goal should cooperate.…”
Section: Institutional and Technical Factors And Market Choices Of Smmentioning
confidence: 99%
“…This part is derived from Masuku and Kirsten (2004); Masuku et al (2003Masuku et al ( , 2007. The Swaziland sugar industry derives its present structure from the Sugar Act of 1967.…”
Section: The Swaziland Sugar Industrymentioning
confidence: 99%
“…Locally, for example, Hardman et al (2002) applied empirical recursive models that showed that high levels of trust lead to high levels of cooperation, and in turn, high levels of commitment to working relationships in the SA fresh apple export value chain. Masuku et al (2004) showed that cooperation depended on trust, and commitment depended on cooperation, between smallholder sugarcane farmers and millers in the Swaziland sugar industry.…”
Section: Introductionmentioning
confidence: 99%